HUBUNGAN PERILAKU GIZI IBU DENGAN STATUS GIZI ANAK USIA 12-59 BULAN DI PEMUKIMAN SEPANJANG REL KERETA API KELURAHAN GAHARU KECAMATAN MEDAN TIMUR TAHUN 2013 - Tince Sitorus; Ernawati Nasution; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACTNutritional problems that occur currently requires many mothers can not ignore itbecause it can have a negative impact . Occurrence of malnutrition and malnutrition amongchildren under five affected by the lack of knowledge and attitude of mothers in the delivery ofthe energy consumption of protein closely related to the development of the child , and childnutritional adequacy .This study aims to determine the relationship of maternal nutrition knowledge andattitude to the consumption of energy and protein on the nutritional status of children under fivewho live in settlements cccalong the railroad tracks in Sub Eaglewood East District of Medan.This research is cross-sectional . Samples were mothers of children aged 12-59 months toddlersas many as 59 people. Analysis by chi square test with α< 0.05 the data.The results of the study found that knowledge of the relationship of energy consumption(p = 0.695), the relationship of knowledge to the protein intake (p = 0.015), the relationship withthe attitude of the energy consumption of protein (p = 0.04), the relationship of energyconsumption and nutritional status (p = 0.028), the association of protein intake with nutritionalstatus (p = 0.431) , the relationship of knowledge and nutritional status (p = 0.021), attitude ofrelationship with nutritional status (p = 0.009) .From the results of this study are expected to mothers or parents of children aged 12-59months , to pay more attention to the nutritional adequacy of the child , which is related to theconsumption of food in the food supply diverse , and also to the Ministry of Health to provide thefacilities and infrastructure for smooth action in the IHC maximum increase in health careKeywords : knowledge , attitude , energy consumption of protein, nutritional status